2011
DOI: 10.1007/s11558-011-9108-7
|View full text |Cite
|
Sign up to set email alerts
|

The United States Congress and IMF financing, 1944–2009

Abstract: Since 1944, United States financing of the International Monetary Fund (IMF) has been appropriated and approved in Congress by roll-call vote. If voting to increase funds to the IMF is viewed as an observable signal of "support" for the IMF, these votes provide a historical record of legislative support for the IMF in the United States. I analyze roll-call voting on IMF financing from 1944 to 2009 at both the aggregate (congressional) and the micro (legislator) levels. At the aggregate level, I show that suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…In the United States, party ideology has played an important role in fiscal policy at the federal level (e.g., Blomberg and Hess 2003;Haynes and Stone 1990;Alesina and Sachs 1988;Krause and Bowman 2005;Broz 2011). Confirming traditional partisan theory, many studies at the state level also find that leftwing politicians pursued more expansionary fiscal policy than rightwing politicians.…”
Section: Policies and Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, party ideology has played an important role in fiscal policy at the federal level (e.g., Blomberg and Hess 2003;Haynes and Stone 1990;Alesina and Sachs 1988;Krause and Bowman 2005;Broz 2011). Confirming traditional partisan theory, many studies at the state level also find that leftwing politicians pursued more expansionary fiscal policy than rightwing politicians.…”
Section: Policies and Institutionsmentioning
confidence: 99%
“…Several studies have shown that party ideology influences economic policy-making in the United States. At the federal level and across the US states leftwing / Democrat governments seem to have pursued more expansionary fiscal policies than rightwing / Republican governments by increasing public expenditures and tax burdens (e.g., Alt and Lowry 1994;Blomberg and Hess 2003;Reed 2006;Rose 2006;Chang et al 2009;Broz 2011;Pickering and Rockey 2013). The result of ideology-induced fiscal policies across the US states is not only meaningful because states have the power to choose different policies and institutions.…”
Section: Introductionmentioning
confidence: 99%
“…At the national level, the relative importance of voting motives has been investigated in a number of studies. Rothenberg and Sanders (2000), Snyder and Groseclose (2000), Kilby (2001, 2002), and Broz (2008Broz ( , 2010 focus on the determinants of the individual voting decision, among many others. Using discrete choice techniques, a distinction can be made between different motives for voting, such as constituent interest, party affiliation, or personal ideology.…”
Section: Towards a Baseline Modelmentioning
confidence: 99%
“…This pattern holds for both branches of the partisan theory -for the classical approach (Hibbs 1977) and for the rational approach (Alesina 1987). Many empirical studies have investigated how electoral motives and government ideology influence economic outcomes (see, for example, Alesina et al 1997, Cusack 1997, Schmidt 2002, Grier 2008, Belke et al 2007, Bjørnskov 2008, Sakamoto 2008, Bodea 2010, Aidt et al 2011, Broz 2011.…”
Section: Ideology-induced Macroeconomic Policies In Germanymentioning
confidence: 96%